Snake venom components enhance pain upon subcutaneous injection: an initial examination of spinal cord mediators - Chacur, Marucia (2004)
Snakebites are a relevant public health problem in Central and South America. Snake bite envenomations cause intense pain, not relieved by anti-venom. The fangs of many species are short, causing subcutaneous injection. Fangs of larger species inflict subcutaneous or intramuscular envenomation. To understand pain induced by subcutaneous venom, this study examined spinal mechanisms involved in pain-enhancing effects of subcutaneous Lys49 and Asp49 secretory phospholipase-A2 (sPLA2), two components of Bothrops asper snake venom showing highly different enzymatic activities. Unilateral intraplantar sPLA2-Lys49 (catalytically inactive) or sPLA2-Asp49 (catalytically active) into rat hindpaws each induced mechanical hyperalgesia (Randall–Selitto test), whereas only catalytically active sPLA2-Asp49 caused mechanical allodynia (von Frey test). Effects induced by both sPLA2s were inhibited by intrathecal fluorocitrate, a reversible glial metabolic inhibitor. In support, immunohistochemical analysis revealed activation of dorsal horn astrocytes and microglia after intraplantar injection of either sPLA2. Spinal proinflammatory cytokines, nitric oxide, and prostanoids each appear to be involved in the pain-enhancing effects of these sPLA2s. Blockade of interleukin-1 (IL1) inhibited hyperalgesia induced by both sPLA2s, while leaving allodynia unaffected. Blockade of tumor necrosis factor reduced responses to sPLA2-Asp49. An inhibitor of neuronal nitric oxide synthase, 7-nitroindazole (7-NI), inhibited hyperalgesia induced by both sPLA2s, without interfering with allodynia induced by sPLA2-Asp49. On the other hand, l-N6-(1-iminoethyl)lysine (l-NI), an inhibitor of the inducible nitric oxide synthase, did not alter any sPLA2-induced effect. Lastly, celecoxib, an inhibitor of cyclooxygenase-2, attenuated sPLA2 actions. These data provide the first evidence of spinal mediators involved in pain facilitation induced by subcutaneous venoms.